Strict Liability Principle: Consumer Protection from Hidden Defective Products in Indonesia - Holijah Holijah (Sriwijaya Law Review, 2020)
Weak supervision on the standardization of the quality of goods products, the negative impact of the use of technology, and fraudulent products cause an increase in hidden defective goods products in the current era of globalization. The phenomenon of the existence of hidden defective products increasingly demanding the importance of the role of government to regulate, supervise and control to create a legal construction of product responsibility for consumers, which normatively does not exist yet. The concept of consumer protection due to hidden defective goods is a new thing that has never been explained in Indonesian literature. The purpose of this paper is to analyze the hidden defective products phenomenon, and the legal basis on the principle of responsibility is applied. Strict liability of produces due to loss of hidden defective goods products as an effort to protect consumers in Indonesia. This research uses the normative analysis method by using secondary data as primary data through the statute approach, philosophical approach, and historical approach. The results of this study show the importance of legal products that can provide consumer rights without reducing the rights of produces. The need for a legal basis for the product liability principle with the principle of strict liability to claim the responsibility of a produces through developing the doctrine of tort as a basis for demanding compensation due to hidden defective goods from the outstanding produces on the market. For this reason, it is recommended as a consideration, namely normative amendment to the law of the Republic of Indonesia number 8 of 1999 concerning consumer protection as a short-term step, while the long-term step is to issue a special law that regulates the absolute responsibility of produces due to loss of defective products hidden in the future.